Examining urban novice college Spanish learners’ perceptions towards hybrid teaching - Capanegra, Ana (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2021)
This study examined the perceptions urban novice college Spanish students have of combining face-to-face instruction with online homework. The study especially analyzed the quality of hybrid learning instruction. The same questionnaire was administered at the beginning and at the end of the study and then the data gathered was compared. The results of the study offered advice especially for non-traditional students. First, the integration of technology in instruction made a significant difference for urban students since the participants expressed a positive attitude towards the use of technology. Second, they found that the practice of the target language at their pace and time was beneficial in class instruction. Third, those participants who expressed having some knowledge of another foreign language benefitted their learning of the language. Fourth, students indicated that they benefited from the quality of instruction given by trained educators.